DISTRIBUSI Pb DAN Cu PADA BERBAGAI UKURAN PARTIKEL SEDIMEN DI PELABUHAN BENOA - Sahara, E. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 2 Juli 2009)
This paper discusses the distribution of Pb and Cu in various particle sizes of sediment collected from Benoa Bay, Bali. The particle sizes of sediment observed were >300; 300 – 100; 100 – 88,88 – 63 and <63 mm. Prior to the determination of both heavy metals, the sediments were digested with the mixture of HNO3 and H2O2 (1:1) at 120oC. The measurements of the metal concentrations were performed by the use of Atomic Absorption Spectroscopy technique with the application of calibration method. It was found that the smaller the particle sizes the higher the metals concentraions were. The sediment of >300 mm contained Pb and Cu 0,74 – 0,77 mg/kg and 0,15 – 9,24 mg/kg, respectively. On the other hand, the sediment of < 63mm contained 21,36 – 53,01 mg/kg Pb and 104,14 – 132,82 mg/kg Cu. It was also observed that the distribution of particle sizes of all sediment collected from four sampling locations had similar patern.
Keywords: distribution, particle size, sediment, Benoa Bay